THE CORRELATION AMONG STUDENTS’ SELF-EFFICACY, ACADEMIC STRESS, AND LEARNING ACHIEVEMENT IN RESEARCH IN ELT COURSE - Kadir, Muhammad Nurul Ikram; Salija, Kisman; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study used two different types of instruments, including a scale test by giving two types of questionnaires to the students and a learning achievement test used by getting the MID-Test score of the students studying Research in ELT course in the undergraduate program, to ascertain the correlation between students' self-efficacy and their learning achievement, as well as the correlation between students' academic stress and their learning achievement. Quantitative research with a correlational design was used in this study. A total of 43 students studying Research in the ELT course in the undergraduate program constituted the sample for this study. Simple random sampling was also used in the sampling process, which carried out randomly regardless of the strata in that population. In this study, the researcher found that the level of students’ self-efficacy with a mean score 70,70; the level of students' academic stress with a mean score 61,81; and the learning achievement of students studying Research in ELT course in the undergraduate program with a mean score 78,72. Students' self-efficacy and learning achievement were positively correlated. This means that the higher self-efficacy in a student is the higher the learning achievement will be. While the correlation between academic stress and learning achievement is negative, it means that the higher the academic stress experienced by students, the lower the learning achievement.